Sequence and structure requirements for the biosynthesis of pseudouridine (psi 35) in plant pre-tRNA(Tyr). - Szweykowska-Kulinska, Z (1992)
All eukaryotic cytoplasmic tRNAs(Tyr) contain pseudouridine in the centre of the anticodon (psi 35). Recently, it has been shown that the formation of psi 35 is dependent on the presence of introns in tRNA(Tyr) genes. Furthermore, we have investigated the structural and sequence requirements for the biosynthesis of psi 35. A number of mutant genes were constructed by oligonucleotide-directed mutagenesis of a cloned Arabidopsis tRNA(Tyr) gene. Nucleotide exchanges were produced in the first and third positions of the anticodon and at positions adjacent to the anticodon. Moreover, insertion and deletion mutations were made in the anticodon stem and in the intron. The mutant genes were transcribed in HeLa cell extract and the pre-tRNAs(Tyr) were used for studying psi 35 biosynthesis in HeLa cell and wheat germ extracts. We have made the following observations about the specificity of plant and vertebrate psi 35 syntheses: (i) insertion or deletion of one base pair in the anticodon stem does not influence the efficiency and accuracy of the psi 35 synthase; (ii) the presence of U35 in a stable double-stranded region prevents its modification to psi 35; and (iii) the consensus sequence U33N34U35A36Pu37 in the anticodon loop is an absolute requirement for psi 35 synthesis. Thus, psi 35 synthases recognize both tRNA tertiary structure and specific sequences surrounding the nucleotide to be modified.